Effect of caregiver burden on anticipatory grief among caregivers of elderly cancer patients: Chain mediation role of family functioning and resilience - Li, Caiyue; Tang, Nan; Yang, Lili; Zeng, Qing; Yu, Tana; Pu, Xiaojin; Wang, Juan; Zhang, Hongchen (Frontiers in Psychology, 2023)
This study aimed to explore the relationship between caregiver burden and anticipatory grief among caregivers of elderly cancer patients, and to examine the chain mediation effects of family functioning and resilience. A total of 624 valid questionnaires were collected. The Structural Equation Model was established to test the mediating effects of family functioning and resilience. Results showed that caregiver burden has a direct positive effect on anticipatory grief, both family functioning and resilience have negative effects on caregiver burden and anticipatory grief, and that resilience moderates the mediating effect of family functioning. Our findings suggest that reducing the caregiver burden among caregivers of elderly cancer patients, improving family functioning, and enhancing resilience have important effects in alleviating the anticipatory grief of caregivers. Our findings provide some references for further research. Medical staff should better understand the grief experience of caregivers and implement interventions to enable caregivers to better cope with anticipatory grief and psychological stress, so as to promote the quality of care for elderly cancer patients.